Nilai Budaya Dalam Nyanyian Ucapan Syukur Pada Tradisi Padungku di Poso Sulawesi Tengah (Suatu Kajian Antropologi Sastra) - Andi Ika Mutmainnah; Nensilianti Nensilianti; Faisal Faisal (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study describes the cultural values contained in the thanksgiving song in the Padungku tradition in Poso, Central Sulawesi and is used as a source of data to be analyzed. This study uses a descriptive qualitative method by describing the data obtained based on the theory used. Sources of data used in this study are various information and information obtained directly from several informants. The data used in this study is a thanksgiving song for the Padungku tradition in Poso, Central Sulawesi. The results of this study indicate that there are four levels in finding the meaning contained in the thanksgiving song in the Padungku tradition, the four levels are: 1) the geographical level, namely the level related to circumstances, 2) the techno-economic level, namely the level related to livelihoods, 3) the sociological level, which explains the relationship between society and 4) the cosmological level, which explains the relationship between humans and the Creator. Meanwhile, the cultural values contained in the thanksgiving songs in the Padungku tradition in Poso, Central Sulawesi, are religious, philosophical and sociological values. The singing also has several functions which include ritual, entertainment and educational functions..Keywords: Literary Anthropology, Cultural Values, Folk Songs.